The Influence of the Extent of Color-Vision Deficiency on Shade-Matching Ability - Boštjan Pohlen; Marko Hawlina; Igor Kopač (University of Zagreb. School of Dental Medicine, 2019)
Objective: To evaluate the influence of the extent of color-vision deficiency on visual shade-matching ability. Materials and methods: Six groups were investigated: the control group (N = 68), the protan medium deficiency (PMED) group (N = 5), the protan strong deficiency (PSTD) group (N = 5), the deutan mild deficiency (DMID) group (N = 5), the deutan medium deficiency (DMED) group (N = 5) and the deutan strong deficiency (DSTD) group (N = 8). The color vision of the participants was evaluated monocularly using the Hardy-Rand-Rittler (HRR) test and on an HMC Anomaloskop MR (Rayleigh test). The final exam on a Toothguide Training Box consisted of 15 lightness-chroma-hue tasks. The color difference (ΔE* ab) and the shade-matching score (ΣΔE* ab) were computed. The means and the standard deviations for the ΣΔE* ab were calculated. An independent t-test was used for statistical analyses of the data and a comparison of means (α = .05) for protan groups and a one-way analysis of variance (ANOVA) and a post-hoc Bonferroni test (α = .05) for deutan groups. Results: The PSTD group had a mean ΣΔE* ab of 63.38 ± 9.52, which means their elections were significantly worse in comparison to the PMED group (ΣΔE* ab = 47.62 ± 9.88, p = 0.033). The selections of the control group were significantly better in comparison to all groups with color-vision deficiency (control - PMED, p = 0.031; control - PSTD, p < 0.0001; control - DMED, p < 0.0001; control - DSTD, p < 0.0001), except in comparison with DMID group (p = 0.082). The comparisons between deutan groups were not significantly different (DMID - DMED, p = 0.352; DMID - DSTD, p = 0.323; DMED - DSTD, p = 1.000). Conclusion: Participants with strong protan color-vision deficiency are worse at shade matching than participants with medium protan color-vision deficiency.